Implementation and Development of an Adaptive Steering-Control System - (:unkn) unknown (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2010)
In this paper, an adaptive steering-control system for a steer-by-wire system, which consists of a vehicle directional-control unit and a driver-interaction unit, is developed. The adaptive online estimation method is used to identify the dynamic parameters of the vehicle directional-control and driver-interaction units. A nonlinear 4-degree-of-freedom (DOF) vehicle model, including the longitudinal, lateral, yaw, and quasi-static roll motions, is derived using Newtonian mechanics to simulate and test the adaptive steering-control system. Experimental results are performed to demonstrate the efficacy of the proposed adaptive steering-control system.
Keywords: Adaptive control; compliance control; steering systems; system identification; vehicle dynamics